Analysis of spontaneous vegetation in semi-arid cattle fields of the middle valley of Río Negro - Peralta, Paola Fernanda (2021)
Fil: Peralta, Paola Fernanda. Universidad Nacional de Río Negro. Escuela de Medicina Veterinaria y Producción Agroindrustrial. CIT. Río Negro, Argentina